2014
DOI: 10.1155/2014/372045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Time and Location of the Silicone Oil Emulsification by Spectral-Domain Optical Coherence Tomography after Silicone Oil Tamponade

Abstract: Purpose. To estimate localization and the period up to the appearance of small hyperreflective round-shaped droplets using spectral-domain optical coherence tomography (SD-OCT) after pars plana vitrectomy with silicone oil tamponade. Methods. A retrospective observational study included 24 patients who had undergone pars plana vitrectomy with silicone oil tamponade for proliferative vitreoretinopathy (PVR) retinal detachment. SD-OCT analysis was performed 1, 3, and 6 months after surgery. We characterized the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…Odrobina et al found hyper-reflective round-shaped droplets at 3 months after SO tamponade by spectraldomain optical coherence tomography and hypothesised that emulsification of SO began within 3 months after surgery. 13 In another study, Toklu et al investigated the natural course of emulsification after SO tamponade in retinal detachment surgery and found that emulsification time ranged from 5 months to 24 months. Since most cases had SO emulsification within the first year, they proposed to extend the silicone oil removal time up to 1 year to achieve a stable retina status in cases with a high risk of redetachment.…”
Section: Discussionmentioning
confidence: 99%
“…Odrobina et al found hyper-reflective round-shaped droplets at 3 months after SO tamponade by spectraldomain optical coherence tomography and hypothesised that emulsification of SO began within 3 months after surgery. 13 In another study, Toklu et al investigated the natural course of emulsification after SO tamponade in retinal detachment surgery and found that emulsification time ranged from 5 months to 24 months. Since most cases had SO emulsification within the first year, they proposed to extend the silicone oil removal time up to 1 year to achieve a stable retina status in cases with a high risk of redetachment.…”
Section: Discussionmentioning
confidence: 99%
“…While emulsification time is believed to largely vary between 5 and 24 months postoperatively ( 32 ), some reports emphasize that first signs of SIO emulsification appear in the first 3 months postoperatively ( 33 ) and even earlier, in the first month postoperatively ( 28 ). Since most of the cases have a certain degree of SIO emulsification within the first year postoperatively, there is a large consensus on the necessity to remove the SIO during this interval.…”
Section: Current State Of Knowledge Regarding Intraocular Pres- Sumentioning
confidence: 99%
“…[11][12][13] Additionally, SD-OCT and swept-source OCT analysis of eyes with SiO tamponade has also revealed the presence of hyperreflective areas located intraretinally and subretinally, which several authors have argued may correlate with possible silicone oil emulsification and deposition. [14][15][16] The aim of this study was to further evaluate and characterize structural retinal changes, particularly outer retinal changes, present on SD-OCT in eyes that have undergone pars plana vitrectomy (PPV) with SiO tamponade.…”
Section: Introductionmentioning
confidence: 99%